Peripapillary Pachychoroid Syndrome (PPS): Diagnosing and Treating a Rare Entity - Peggy Bouzika; Ilias Georgalas; Maria-Evanthia Sotirianakou; Aristotelis Karamaounas; Chrysanthos Symeonidis; Konstantinos Tyrlis; Stylianos Blounas; Ekaterini Mani; Tryfon Rotsos (Case Reports in Ophthalmological Medicine)
Two cases with peripapillary pachychoroid syndrome (PPS) along with the challenges concerning correct diagnosis and treatment are presented. In the first case, the patient presented with painless unilateral gradual visual loss. Fundoscopy and optical coherence tomography (OCT) revealed cystoid macular edema (CME) in the left eye (LE), extending from the temporal optic disc margin towards the fovea, with no additional findings. Enhanced-depth imaging- (EDI-) OCT provided additional information and increased choroidal thickness nasally to the macula and pachyvessels in the outer choroidal layer, findings supportive of PPS. Photodynamic therapy (PDT) was applied at the leakage sites. Two months later, CME and subretinal fluid (SRF) had resolved, and VA had significantly improved. In the second case, a patient presented with reduced vision and metamorphopsia bilaterally over the previous 5 days. Fundoscopy revealed CME in both eyes. OCT confirmed the presence of CME in the papillomacular area in the right eye; similarly, CME was recorded in the macula of the LE with SRF located subfoveally. EDI-OCT showed increased choroidal thickness in both eyes. Treatment was administered, originally with dorzolamide eye drops along with eplerenone tablets, and then dexamethasone eye drops that eventually led to significant anatomic and functional improvement. It is important for ophthalmologists to be able to recognize the unique clinical entity of PPS, as its resemblance to disorders with similar features may lead to misdiagnoses and unnecessary, or even incorrect, interventions.